POLA SEBARAN CAFÃ HOTSPOT DI YOGYAKARTA - , VITA DEWI KARUNIASARI; , Prof. Ir. Bambang Hari Wibisono, MUP.,M.Sc.,Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2012)
In the past 10 years the growth of cafes in Yogyakarta berhotspot very sharp. However, this growth, tend to be controlled and directed. This study uses the method of survey design with an emphasis on descriptive explanatory type of research. This study aims to determine the distribution patterns café hotspot in Yogyakarta. Research objectives to be achieved, namely to identify distribution patterns café hotspot in Yogyakarta. Territorial scope of this study is in the agglomeration of Yogyakarta. Distribution patterns hotspot cafes in Yogyakarta can be categorized into 4 (four) parts: distribution pattern that is concentric, linier, jumps, and spreads are not included into the category of concentric, linier, and jumping. The factors that influence the spread of hotspots in Yogyakarta café is Population, ease of access to the café, market demand and business opportunities and ease of licensing.